A formação continuada de professores de português : uma abordagem discursiva do Gestar II - Costa, Gláucia Rejane da (2011)
This work discusses the continued formation of Portuguese teachers, called Gestar II, promoted by Brazilian Government and the Portuguese teaching, considering the control mechanisms according to Foucault (2003). In this perspective, it studies the closed politics, according Mendonça (2006), verifying the way they act against the language teaching in its heterogeneity. In this context, based on Discourse Analysis postulations, this study discusses the naturalization of the relation between theory and practice, conception observed in the documents of the program. The author uses the Enunciation Theory in order to verify the dialogical relation which occurs in this process of formation besides the discursive genres used in its situations of interaction. In this way she analyses some activities proposed by the didactical material from Gestar II. The author searches the discursive formations (DFs), based on subjects enunciation, observing possible DFs superpositions‟, as known by Foucault‟s (1997) postulates, that the DFs has no limits. And concerned in Discourse Analysis, observes the DFs, already mentioned, the subject‟s constitution, the different notions of the subject and its relation with the discourse, ideology and sense. By that way, the present study is circunscript in Discourse‟s Linguistic. Besides this, she compares the discourses enunciated by the teachers who took part in the process of formation and those ones which Gestar II enunciates from its documents. In this study, she attempts to their images about the program, the theory/practice relation and Portuguese teaching. In this way, she verifies that the first ones are clearly affected by the last ones, which confirms the control of the discourses produced by teachers and institutions. Besides that, it reflects a power relation institutionally established.